Effects of Carbon/Nitrogen Ratio on Growth, Intestinal Microbiota and Metabolome of Shrimp (Litopenaeus vannamei) - Guo, Haipeng; Huang, Lei; Hu, Songtao; Chen, Chen; Huang, Xiaolin; Liu, Wei; Wang, Sipeng; Zhu, Yueyue; Zhao, Yueji; Zhang, Demin (Frontiers in Microbiology, 2020)
Increasing the C/N ratio of input feed has been reported as a practical approach for improving water quality and enhancing shrimp growth through changing the bacterial community of rearing water. However, little is known about the effects of different C/N ratios of feed input on the intestinal microbiota and metabolome of shrimp. In the present study, the effects of three different C/N ratio levels (CN6, CN10, and CN15) maintained by adding sucrose on the growth, intestinal microbiota and metabolome of Litopenaeus vannamei, and bioflocs formation were investigated after 17 days of feeding. The results indicated that higher C/N ratio (10 and 15), especially CN15, of feed input significantly enhance the length and weight of shrimp individuals accompanied by a significant accumulation of bioflocs, compared to that of CN6. The increase of C/N ratio input decreased the α-diversity of the intestinal microbiota and changed the microbial community structure through increasing the relative abundance of Actinobacteria, Rhodobacteraceae (mainly consist of Roseobacter and Paracoccus groups), Alteromonadaceae, and inhibiting the growth of Cyanobacteria, certain Rhodobacteraceae, Mycoplasmataceae and Vibrio. The change of microbial community caused by increasing C/N ratio input was closely associated with various bioactive metabolites of flavonoids, benzenoids, prenol lipids, and indole derivatives, which are benefit for shrimp growth either as an antimicrobial agent or as a nutrient component. Overall, this study demonstrated that manipulating high C/N ratio of feed input helps to the growth of shrimp through increasing the relative abundance of potential beneficial bacteria and the accumulation of various bioactive metabolites to suppress the growth of detrimental bacteria.